DIMENSI-DIMENSI KONTEKSTUAL DI DALAM PENULISAN BUKU TEKS PELAJARAN BAHASA INDONESIA - suryaman, maman (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
This article is about a study on what basically a lesson book is and how acontextual teaching strategy is applied in writing a lesson book of the languagecalled Bahasa Indonesia. In involving students in language learning and literaryactivity, a competency to be developed is related to how to guide them so that theyare motivated to learn through the lesson book. A basic principle to be paidattention to is that students are able to build up experiences in language and literaryactivities on the basis of their initial experience.The study indicates the following results. First, a lesson book is ahandbook for students at a level of formal education and used as an instructionalmedium related to a certain subject matter (such as Bahasa Indonesia). Second,such a book occupies a very important position as a store of knowledge of variousaspects of life, has a meaningful role in students' learning achievement, andconstitutes a source of reference for the teacher. Third, that book should contain afoundation for a clear and contemporary viewpoint, materials that are adequate,systematically and gradually composed, presented via methods and means able tostimulate students to read books with interest, having enough depth providingthem with help in solving academic problems, and enabling them to have a chanceto ponder what they have learned, and also evaluation instruments enabling themto know the competency they have achieved. Fourth, the curriculum containsinformation of only the main competencies to be achieved and these still have to beinterpreted, clarified, broken down, completed, enriched, and put together througha lesson book. Fifth, the students, teacher, teaching materials, ways of presentingthem, and exercises are the important components of learning to be accommodatedin a lesson book. Sixth, contextual teaching employs a strategy oriented to effortsof aiding and inspiring students by linking a standard of competency with a realworldsituation. Seventh, the basic principles of a contextual teaching approach areproblem-based learning, context-based learning, difference-based learning,learning based on individuals, learning based on groups, and learning based onauthentic evaluation. Eighth, a contextual teaching strategy could be manifested ina lesson book of Bahasa Indonesia by providing such activities as investigation,exploration, inquiry, model making, construction, and reflection. Ninth, anapplication of such a strategy should be in a concrete form to enable students tobuild up effective new experiences.Keywords: lesson book of Bahasa Indonesia, contextual dimension, contextualstrategy165